2020
DOI: 10.3390/v12101157
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Noroviruses throughout Outbreaks in Germany 2018

Abstract: Human norovirus accounts for the majority of viral gastroenteritis cases worldwide. It is a fast evolving virus generating diversity via mutation and recombination. Therefore, new variants and new recombinant strains emerge in the norovirus population. We characterized norovirus positive stool samples from one intensively studied district Märkisch-Oderland state Brandenburg with the samples from other states of Germany in order to understand the molecular epidemiological dynamics of norovirus outbreaks in Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…The most prevalent NoV genotype was GII.P31-GII.4 Sydney, with a 45.2% detection rate. This finding is consistent with the results reported in Germany, Brazil, and China [ 26 , 44 , 45 ]. Surprisingly, we did not find that the emerging recombinant strain GII.P16-GII.4 replaced GII.P31-GII.4 Sydney around the world [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most prevalent NoV genotype was GII.P31-GII.4 Sydney, with a 45.2% detection rate. This finding is consistent with the results reported in Germany, Brazil, and China [ 26 , 44 , 45 ]. Surprisingly, we did not find that the emerging recombinant strain GII.P16-GII.4 replaced GII.P31-GII.4 Sydney around the world [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…More generally, we found a lower prevalence of NoV in our study compared to that reported in all previous studies from neighboring countries [33,37]. As observed elsewhere, GI strains were less frequently detected and had a higher diversity than GII genogroups [26,30,41]. The predominance of the GII.4 variants in this study may reinforce the hypothesis and emphasize the need to explore whether new GII.4 variants possibly arise in Africa where some of the GII.4 variants circulated earlier [24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A larger GII genetic diversity was observed for both polymerase types and capsid genotypes compared to GI. The most predominant genotype detected was GII.4 Sydney[P16] followed by GII.2[P16] and GII.4 Sydney[P31], in agreement with several studies performed world-wide [ 18 , 19 , 54 , 61 , 62 , 63 , 64 , 65 ]. In 2017, we observed a high circulation of the GII.2[P16] at almost similar proportions of GII.4[P16].…”
Section: Discussionsupporting
confidence: 85%
“…In regard to age groups, we observed the highest prevalence of norovirus infections in children aged group from >6 to 24 months old. Several studies have demonstrated the peak of norovirus infection within the same age range [ 50 , 51 , 52 , 53 , 54 ]. Similar to our data, a study performed in Belém, Brazil, from 2012 to 2015 with children hospitalized with AGE, found the majority of norovirus-positive cases (72.7%) among the age group between 6 and 24 months old [ 29 ].…”
Section: Discussionmentioning
confidence: 99%